Bimbingan Keagamaan dan Dampaknya terhadap Sikap Keagaamaan Muallaf di Panti Asuhan Al-Falah - Napri Napri (WARAQAT : Jurnal Ilmu-Ilmu Keislaman, 2021)
Mu'allaf is classified as a person who needs religious guidance, on the basis of these needs Al-Falah Koto Tangah orphanage has a program oriented towards increasing mu'allaf knowledge of Islamic teachings. The results of this religious guidance should be practiced by every mu'allaf. Therefore, this study aims to describe how the impact of religious guidance on religious attitudes mu'allaf. The research was conducted with a qualitative approach, data sources included orphanage caregivers and mu'allaf in al-Falah orphanage. Data is collected through observation, interview and documentation studies, all data is analyzed through data reduction, classification, presentation and interpretation and withdrawal of conclusions. The results of the study were mu'allaf in orphanages getting religious guidance in aspects of prayer, reading the Qur'an, practicing sunnah worship and morals. The existence of various forms of guidance, mu'allaf in al-Falah orphanage is able and memorizes the readings and movements of prayer, has the ability to read the Qur'an, know and have good morals